Myelodysplastic syndromes in South America: A multinational study of 1080 patients - Belli, Carolina Bárbara (2015)
There are previously reported data describing differences between Asian and European patients with Myelodysplastic Syndromes (MDS), few direct comparisons based on cancer registration characteristics or using cohorts to validate scoring systems. This is the first study from South-America, which attempts to describe demographic, clinical features, and outcome of MDS patients. We retrospectively analyzed 1,080 patients with de novo MDS from Argentina (635), Brazil (345), and Chile (100). Chilean patients were younger (P=0.001) with female preponderance (P=0.071). Brazilian series showed a higher predominance of RARS subtype regarding FAB and WHO classifications (P<0.001). Hemoglobin levels were significantly lower in Brazilian and Chilean series (P<0.001), and Chilean series also showed a lower platelet count (P=0.028), with no differences concerning the neutrophil count, % BM blast, and the distribution of cytogenetic risk groups (P>0.05). Chilean series depicted a lower overall survival (OS; 35 months vs. 56 months-Argentine; 55 months-Brazil, P=0.030), which was consistent with a higher predominance of the high-risk group according both to the IPSS and IPSS-R (P=0.046 and P<0.001). The IPSS-R system and its variables showed a good reproducibility to predict clinical outcome for the whole South-American population. Epidemiological and clinical characteristics, distribution among prognostic subgroups, the OS, and the access to disease modifying therapies were more similar between Argentinean and Brazilian compared with Chilean MDS series. This will need further analysis in a larger group of patients. Descriptive and comparative studies are necessary to establish epidemiological features useful for public health attitudes to generate suitable therapeutic schemes.